Difficulties of Understanding English Breaking News Headlines by Iraqi EFL Learners at the University Level: عبد القادر طالب نعيم, و جمعة قادر حسين (Journal of the College of Education for Women, 2021)
Understanding breaking news necessitates a special attention, since they are written with a special style. The study aims at identifying the difficulties faced by the Iraqi university EFL learners in comprehending English breaking news. The study included 10 fourth year students enrolled at the Department of English, College of Education for Humanities, University of Anbar. Thus, a questionnaire as a research instrument, was sent online to the students. The questionnaire points were related to the identification of difficulties faced by the learners in comprehending English breaking news. The data of the study were (10) headlines selected purposively from Euronews website. The data were qualitatively analyzed based on quantifying the quality procedure. The findings showed that (54%) of the total number of the students stated that the headlines are difficult to understand, and (46%) considered them easy. Based on these findings, the study has concluded that students faced four main difficulties: neologism, difficult vocabulary, ellipsis, and passive voice when reading news headlines. Neologism has scored the highest percentage (32.4324%), while passive voice has been the lowest (5.4054%).